Profile of E-STATPHYS Assisted PBL Model on Static Fluid Material to Improve Problem-Solving Skills of High School Students - Siska Agustin Sha Hareni; Binar Kurnia Prahani; Dhea Wanda Irani; Elvia Reza Lutfiani; Nurul Muawiyah; Nofri Hidayatin; Noer Risky Ramadhani (Journal of Innovative Technology and Sustainability Education, 2026)
Objective: This study aims to analyze the problem-solving skills of high school students as a basis for considering the application of the Problem Based Learning (PBL) model assisted by the E-STATPHYS digital book on static fluid material. Method: This study used a qualitative descriptive method with 105 grade XI students at SMA Negeri 1 Kedungpring as subjects. Data collection techniques included a preliminary survey in the form of a problem-solving skills test, student response questionnaires, and interviews with physics teachers. Data were analyzed to identify the level of students problem-solving skills. Results: The results showed that 98 students were in the low problem-solving skills category, 7 students were in the medium category, and there were no students in the high category. These findings indicate that students problem-solving skills on static fluid material still need to be significantly improved. Novelty: The novelty of this study lies in the use of the results of the initial analysis of problem-solving skills as a basis for the development and application of the Problem Based Learning model assisted by the E-STATPHYS digital book, which is specifically designed to support physics learning on static fluid material and facilitate the improvement of students problem-solving skills.